2007
DOI: 10.11606/issn.1679-9836.v86i2p94-100
|View full text |Cite
|
Sign up to set email alerts
|

Acidentes por queda de laje na infância registrados no Hospital Estadual do Grajaú em 2005

Abstract: Os acidentes têm aumentado as taxas de morbimortalidade infantil, tornando-se importante problema de saúde pública. Pouco precisos, os dados epidemiológicos dificultam o direcionamento das medidas preventivas. A finalidade deste estudo é determinar a freqüência dos acidentes por queda de laje em menores de 13 anos internados no Hospital Estadual doGrajaú em 2005, e propor ações preventivas na região. Realizou-se estudo retrospectivo, avaliando-se os atendimentos infantis por trauma, em especial as quedas de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Percentage distribution of monthly frequencies of cases of falls from roof slabs over the study period relationship between falls from roof slabs and serious injuries. 7,13,16,18 Campos et al 7 found that falls from concrete roof slabs were the main mechanism for spinal cord injuries among people under the age of 20 years, as well as the main mechanism for trauma affecting the cervical spine at any age. Gonçalves et al 16 also presented data that placed this type of fall as the primary cause of spinal cord injuries, representing 25% of all causes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Percentage distribution of monthly frequencies of cases of falls from roof slabs over the study period relationship between falls from roof slabs and serious injuries. 7,13,16,18 Campos et al 7 found that falls from concrete roof slabs were the main mechanism for spinal cord injuries among people under the age of 20 years, as well as the main mechanism for trauma affecting the cervical spine at any age. Gonçalves et al 16 also presented data that placed this type of fall as the primary cause of spinal cord injuries, representing 25% of all causes.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,7,12,13 This applied especially to the age group of children and adolescents, because these individuals are more exposed to this type of trauma. In the scientific literature, there is a lack of studies characterizing this type of accident and promoting measures to prevent these falls.…”
Section: Tipo De Estudo E Localmentioning
confidence: 99%
See 2 more Smart Citations
“…Between the years 2000 and 2006, Campos et al (2008) observed that >60% of spinal trauma admitted to Heliópolis Hospital, located near the second-largest slum in São Paulo, was due to unintentional falls, with falls from slabs accounting for almost one-third of these cases. Aranha et al (2007) pointed out that in the hospital of the most populous district of the city of São Paulo, of the total hospital admissions for fall accidents in children under 13 years of age, falls from slabs accounted for almost 10%, which are more common on weekends when children spend more time at home. In another study conducted in the second-largest slum in São Paulo, Waksman et al (2014) showed that of the total number of fall accidents among children up to 15 years of age, 55% were from families with more than six people living in dwellings with up to three rooms.…”
Section: Introductionmentioning
confidence: 99%